2022
DOI: 10.3390/powders2010001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Silica Nanofluids at High Salinity and High Temperature

Abstract: Nanoparticles have shown great potential in many sectors of the oil and gas industry, including enhanced oil recovery (EOR). They can be used to improve water flooding by altering the wettability of the porous medium, reducing the interfacial tension, blocking pores, or preventing asphaltene precipitation. Ensuring the stability of nanofluids injected into reservoirs is essential and a great challenge. However, high temperature favors particle collisions and high salinity (ionic strength) decreases electrostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The fact that both materials exhibit a similar pH-dependent adsorption trend suggests that Al-bridged siloxanes play a role in the capture in both materials by making the surface negatively charged. Hutin et al reported that the negative charge on the silica surface is compensated by hydronium ions in an aqueous solution with a low pH and that exchange of the hydronium ions and cations occurs at around pH ≥ 5 . This mechanism explains that all our samples showed an increase in Yb adsorption around pH ∼ 5.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The fact that both materials exhibit a similar pH-dependent adsorption trend suggests that Al-bridged siloxanes play a role in the capture in both materials by making the surface negatively charged. Hutin et al reported that the negative charge on the silica surface is compensated by hydronium ions in an aqueous solution with a low pH and that exchange of the hydronium ions and cations occurs at around pH ≥ 5 . This mechanism explains that all our samples showed an increase in Yb adsorption around pH ∼ 5.…”
Section: Resultsmentioning
confidence: 53%
“…Hutin et al reported that the negative charge on the silica surface is compensated by hydronium ions in an aqueous solution with a low pH and that exchange of the hydronium ions and cations occurs at around pH ≥ 5. 56 This mechanism explains that all our samples showed an increase in Yb adsorption around pH ∼ 5. But the fact that despite having significantly low hydroxyl content in MCM-22 materials compared to kaolinite, the materials show comparable adsorption capacities which suggests that the BAS might play a role in REE capture for MCM-22.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…A higher formation temperature causes faster NP agglomeration, resulting in weakened stability of NPs. High temperatures lead to higher kinetic energies and collision frequencies of nanoparticles, which contribute to the aggregation of nanoparticles and adversely affect their stability . A study by Zhou et al investigated the stability of nanoparticles under different temperatures.…”
Section: Influence Of Chemical Structures In Fluid–fluid and Fluid–ro...mentioning
confidence: 99%
“…It is due to the formation of a monolayer of surfactant that the surface charges of the NPs cannot interact with each other, and the interactions between all NPs will be determined by the surfactant adsorbed on them. In H + protection, Hutin et al 40 investigated the stability of silica nanofluid at different pH values to evaluate its influence. It was concluded that silica nanofluids at a high ionic strength (42 000 ppm of NaCl and seawater) are stable for 1 day at basic pH and 3 weeks at pH 1.5, respectively.…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%
See 1 more Smart Citation